[Interior of Sierra Madre Dorm, Tower 4], circa 1986 (1986)
Two female students seated on top of one of the Sierra Madre dorm room beds. Posters of 'Top Gun' and Tom Cruise can be seen on the walls. A Kermit-the-Frog telephone is viewed atop the dresser (right). On the windowsill there is a small TV with rabbit ears and a stereo with plush 'Alvin and the Chipmunks' on top. The bed cover is decorated with 'Alvin and the Chipmunks'. A dream catcher decorated with dolphins can be seen hanging above the windowsill.